Intracoronary acetylcholine spasm testing: differences in epicardial coronary artery response between smooth and atherosclerotic coronary arteries. (25th November 2020) - Gollwitzer, R; Martinez Pereyra, V; Seitz, A; Bekeredjian, R; Sechtem, U; Ong, P
Abstract: Background: Coronary artery spasm is an established cause for angina pectoris. Epicardial coronary spasm may occur in patients with obstructed as well as unobstructed coronary arteries. Previous studies have suggested that epicardial plaque/atherosclerosis is a prerequisite for the development of epicardial spasm. The aim of the present study was to compare the results of intracoronary acetylcholine (ACh) testing in patients with signs and symptoms of myocardial ischemia with completely smooth versus atherosclerotic yet unobstructed epicardial arteries. Methods: Between 2008 and 2016 a total number of 617 patients with signs and symptoms of myocardial ischemia yet unobstructed epicardial arteries (<50% epicardial stenosis) was included in the present study (mean age 61±11, 61% female). All patients underwent invasive diagnostic coronary angiography followed by intracoronary ACh testing according to a standardized protocol. The ACh-test was considered "positive" in the presence of (a) angina, ischemic ECG shifts during the test and ≥75% focal or diffuse coronary diameter reduction ("epicardial coronary artery spasm") or (b) ischemic ST-shifts and angina in the absence of epicardial spasm ("microvascular spasm"). All angiograms were assessed regarding any visible epicardial plaque/atherosclerosis in a blinded fashion and patients were categorized into those with completely smooth versus those with atherosclerotic coronary arteries. The analysis included 179 patients (29%) with epicardial spasm and 172 patients with microvascular spasm (28%). The remaining 266 patients (43%) had an uneventful or an inconclusive ACh-test result. Results: There were 389 patients (63%) with completely smooth epicardial arteries. The remaining 228 patients (37%) had non-obstructive epicardial plaques <50%. Patients with smooth arteries developed epicardial spasm in 24%, microvascular spasm in 32% and a negative/inconclusive test result in 44% of cases. Patients with atherosclerotic arteries developed epicardial spasm in 38%, microvascular spasm in 21% and an inconclusive/negative test result in 41% of cases. On univariate analysis the presence of epicardial atherosclerosis was associated with epicardial spasm (p=0.006) whereas this was not the case for microvascular spasm (p=0.094). Multivariate analysis revealed the presence of epicardial atherosclerosis (OR 1.921, CI 1.285–2.871, p=0.001) as well as female sex (OR 1.526, CI 1.024–2.274, p=0.038) as independent predictors for epicardial spasm. Conclusion: In patients with signs and symptoms of myocardial ischemia yet unobstructed coronary arteries the presence of epicardial atherosclerosis is an independent predictor for the occurrence of epicardial spasm but not microvascular spasm on acetylcholine testing. Funding Acknowledgement: Type of funding source: Foundation. Main funding source(s): Robert-Bosch-Stiftung, Berthold-Leibinger-Stiftung